A scoping review of feasibility, cost-effectiveness, access to quality rehabilitation services and impact of telerehabilitation: A review protocol. (February 2022) - Nizeyimana, Eugene; Joseph, Conran; Louw, Quinette A
Background: Telerehabilitation is an emerging segment of telehealth and telemedicine that has a potential to deliver quality, accessible, cost-effective and efficient rehabilitation services where geographical distance is a critical factor. The objectives of this review are: to describe the feasibility and cost-effectiveness of telerehabilitation, to scope to what extent telerehabilitation has the potential impact on access to quality of rehabilitation services with specific references to low to middle income countries, and to understand key process factors including barriers and facilitators relevant to the implementation of telerehabilitation. Methods: A scoping review of the literature will be conducted. An electronic search literature will be conducted in PubMed, Scopus, Cochrane library, Africa-wide information, CINAHL, MEDLINE, ProQuest, Web of science and reference lists. The review team will develop a data charting form and pilot it on four randomly-selected studies. The form will be refined based on the results of the piloted articles. Studies identified will be screened at the title and abstract levels by the first reviewer, followed by an independent verification for the accuracy and eligibility by two more reviewers prior to obtaining the full texts. Studies to be included must report on feasibility, cost-effectiveness, access to rehabilitation services, implementation process factors including barriers and facilitators of telerehabilitation. The analysis will include both descriptive summary and inductive thematic analysis. Conclusion: Telerehabilitation has ability to change the current standard of care and allow for improved access and health outcomes in cost-effective ways, while addressing the scarce and unequal distribution of limited number of healthcare providers especially in low to middle income country settings. Thus, the research findings could be used by different stakeholders including: researchers, clinicians, policy makers, and implementation teams as they determine the appropriate setup for new telerehabilitation programs.